Causal relationships between plasma lipidome and diabetic neuropathy: a Mendelian randomization study - Wang, Zhaoxiang; Liu, Zhong; Yang, Qichao; Qiao, Huibo; Yin, Yong; Zhao, Zhiyong; Shao, Xuejing (Frontiers in Endocrinology, 2025)
BackgroundDyslipidemia is closely related to diabetic neuropathy. This study examined the potential causal relationship involving 179 lipid species and the disease.MethodsThe pooled data on 179 lipid species and diabetic neuropathy were obtained from previous genome-wide association studies (GWAS). A Mendelian Randomization (MR) method was employed to investigate the potential causal link, and the robustness of the findings was confirmed through comprehensive sensitivity analyses.ResultsGenetically, phosphatidylcholine might be associated with the risk of diabetic neuropathy. Upon adjusting for multiple comparisons, higher levels of phosphatidylcholine (16:0_20:2) (OR = 0.82, 95%CI: 0.73-0.91; P < 0.001, FDR = 0.033) and phosphatidylcholine (16:1_18:1) (OR = 0.77, 95%CI: 0.67-0.88; P < 0.001, FDR = 0.019) are associated with a decreased risk of diabetic neuropathy. Further multivariable MR (MVMR) analysis demonstrated the effect of genetically predicted phosphatidylcholine (16:1_18:1) remained after adjusting for body mass index (BMI) and glycated hemoglobin (HbA1c). Sensitivity assessments have confirmed the robustness of these findings, revealing no evidence of heterogeneity or pleiotropy.ConclusionOur research linked certain lipid species with diabetic neuropathy risk, suggesting that targeting lipids could be a therapeutic strategy in clinical trials addressing this condition.